Metabolic rhythms in adolescents with diabetes during treatment with porcine or human insulin. Issue 4 (April 1986) - Hocking, M D; Crase, J; Rayner, P H; Nattrass, M
Abstract : Metabolic rhythms were studied over 24 hours in eight adolescent diabetic patients during treatment with porcine insulin and after transfer to human insulin. Despite an increase in dose with human insulin no significant changes were found in fasting blood glucose, 24h mean blood glucose, or glycosylated haemoglobin concentrations. Significantly higher 24h mean blood lactate concentrations and lower total ketone bodies and glycerol concentrations were observed during treatment with human insulin. These findings are consistent with the increase in insulin dose and do not necessarily imply different metabolic responses to species differences in insulin.